The Protective Effects of Annexin A1 in Acute Lung Injury Mediated by Nrf2 - Hui Huang; Yuqin Shi; Yuequan Zhou (Immunity, Inflammation and Disease)
ABSTRACT Background Acute lung injury (ALI), one of the most severe respiratory system diseases, is prevalent worldwide. Annexin A1 (AnxA1) is an important member of the annexin superfamily, known for its wide range of physiological functions. However, its potential protective effect against lipopolysaccharide (LPS)‐induced ALI remains unclear. Materials and Methods Mice were divided into four groups: Sham, LPS + vehicle, LPS + 0.1 μg AnxA1, and LPS + 0.5 μg AnxA1. Lung injury was assessed through histopathology, pulmonary wet‐to‐dry (W/D) ratio, cell counting of bronchoalveolar lavage fluid (BALF), oxidative stress analysis, and noninvasive pulmonary function testing. Gene and protein expression levels were measured using RT‐PCR, ELISA, and western blot analysis. Results AnxA1 alleviated LPS‐induced ALI by protecting lung tissue from damage, reducing the lung wet/dry (W/D) weight ratio, and improving LPS‐induced impaired lung function. Interestingly, administration of AnxA1 was found to repress the infiltration of inflammatory cells by decreasing the total cell count, neutrophils, and protein concentrations in bronchoalveolar lavage fluid (BALF). AnxA1 mitigated the inflammatory response in the pulmonary tissue by lowering the levels of IL‐1β, IL‐6, and TNF‐α in BALF of ALI mice. Additionally, AnxA1 attenuated oxidative stress in lung tissues of ALI mice by restoring the activity of catalase (CAT), SOD, and glutathione (GSH) but reducing the levels of malondialdehyde (MDA). We also found that AnxA1 suppressed activation of the NLRP3 signaling pathway. Mechanistically, AnxA1 activated the Nrf2/HO‐1 signaling pathway while preventing the activation of NF‐κB. Conclusion Collectively, these findings suggest that AnxA1 alleviates LPS‐induced ALI and might be a promising novel therapeutic agent against LPS‐induced ALI.